Development of egg incubator monitoring system using thingspeak as database - Azamir, Irwan Mazwan; Subramaniam, Tamil Selvan; Fairuz, Wan Mohamad (2021)
Temperature and humidity detection are a technique that can be used in a variety of applications, including agriculture, monitoring and health. This project focuses on the development of temperature and humidity monitoring systems on egg incubator machines especially those that require continuous monitoring. The methodology chosen to implement this project was to use the Design Thinking model, part of the Internet of Things technology which is the Thingspeak website as a database to the developed system, Arduino UNO microcontroller, sensors used are DHT22 and HC-SR501 to detect temperature, humidity and movement of the egg incubator machine. Programming process using Arduino IDE and at the same time using C language in the programming. The Arduino UNO microcontroller was connected to the output of the WiFi Module ESP8266 as a transmission system to send data to the database and will display the data in the form of graphs on the display of websites and apps on the user's smartphone as a monitoring tool. The result of this project has produced the graph of data reading output on the display on mobile phones and shows the temperature, humidity and 0 is equal to no movement data, 1 is equal to movement. As a result of this developed project, it could achieve the desired output that were able to read the temperature, humidity and movement and then stored in the database. In conclusion, this product as an innovation that can monitor the temperature, humidity, and movement of the egg inside the incubator machine through the graph data display created and applied only through the smartphone display.